METHODS OF IMPLEMENTATION OF INFORMATION PROTECTION SYSTEM (Journal of Universal Science Research, 2023)
In this article, legal methods of information protection and the main directions of security for electronic computing.  In addition, it provides information about the type of confidential information and the principles of their operation.